2008
DOI: 10.1590/s1413-70542008000100004
|View full text |Cite
|
Sign up to set email alerts
|

Caracterização isozimática e atividade de peroxidase em folhas de plantas hiperídrica, intermediária e normal de Bidens pilosa L. mantidas in vitro

Abstract: RESUMOForam caracterizadas as plantas: hiperídrica, intermediária e normal de um clone de Bidens pilosa mantido em cultivo in vitro por meio de isozimas e da atividade de peroxidase. Empregando-se a eletroforese em géis de amido a 12%, testou-se seis isozimas, sendo detectado polimorfismo em peroxidase e fosfatase ácida, permitindo caracterizar cada tipo de planta. Não houve polimorfismo em fosfogluco isomerase, fosfoglucomutase, glutamato oxaloacetato transaminase e malato desidrogenase. A atividade da peroxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 8 publications
0
4
0
2
Order By: Relevance
“…Regarding the activity of the superoxide dismutase in the foliar and root tissues of the C. langsdorffii seedlings (Figure 6(a) and Figure 6(b)), it can be observed that, although they presented similar results, particularly in those seedlings flooded for 42 and 84 days throughout the experiment, the differences were more expressive in the leaves than in the roots, which allows to infer that this enzyme assumes different functions in different organs or cell compartments of the plants with different routes to the best adaptation to the environment [31] [32]. In the seedlings flooded for 42 days, it was observed that the enzymatic activity was more intense soon after the removal of the flooding condition suggesting a protective adaptation to this type of stress, which is confirmed, over time, The chlorophyll values of seedlings flooded for 63 and 84 days also decreased during the whole recovery period (Figure 7(c)), a direct expression of the damages caused by flooding, since conditions of water stress can favor the reduction of the contents of the photosynthetic pigments due to the oxidative damages they cause [36].…”
Section: Discussionmentioning
confidence: 79%
“…Regarding the activity of the superoxide dismutase in the foliar and root tissues of the C. langsdorffii seedlings (Figure 6(a) and Figure 6(b)), it can be observed that, although they presented similar results, particularly in those seedlings flooded for 42 and 84 days throughout the experiment, the differences were more expressive in the leaves than in the roots, which allows to infer that this enzyme assumes different functions in different organs or cell compartments of the plants with different routes to the best adaptation to the environment [31] [32]. In the seedlings flooded for 42 days, it was observed that the enzymatic activity was more intense soon after the removal of the flooding condition suggesting a protective adaptation to this type of stress, which is confirmed, over time, The chlorophyll values of seedlings flooded for 63 and 84 days also decreased during the whole recovery period (Figure 7(c)), a direct expression of the damages caused by flooding, since conditions of water stress can favor the reduction of the contents of the photosynthetic pigments due to the oxidative damages they cause [36].…”
Section: Discussionmentioning
confidence: 79%
“…It is known, however, that adaptation to water stress might be related to the ability of plants to maintain high levels of antioxidants in their tissues, such as the enzymes superoxide dismutase, peroxidase, and catalase, thus, activity of such enzymes constitutes an important parameter for quantifying plant responses to environmental stresses (Shao et al 2007, Oliveira et al 2008, Pompelli et al 2010, Taiz and Zeiger 2013.…”
Section: An Acad Bras Cienc (2017) 89 (4) Water Availability In the Mmentioning
confidence: 99%
“…Peroxidase activity, an indicator of oxidative stress, was analyzed with the methodology described by Oliveira et al (2008), with adaptations. Absorbance was read using a microplate reader for 96 wells (Microplate) at 492 nm; each reading was taken twice with a 2-min gap between readings.…”
Section: Methodsmentioning
confidence: 99%
“…NS = variation, but not only for peroxidase activity. The change in value obtained allowed for the verification of peroxidase activity, which is determined by changes from 0.01 to 0.02 u.a./min (Oliveira et al, 2008). …”
Section: Test Of Pigments Determinationmentioning
confidence: 99%